2013
DOI: 10.1371/journal.ppat.1003453
|View full text |Cite
|
Sign up to set email alerts
|

The Th17/Treg Ratio, IL-1RA and sCD14 Levels in Primary HIV Infection Predict the T-cell Activation Set Point in the Absence of Systemic Microbial Translocation

Abstract: Impairment of the intestinal barrier and subsequent microbial translocation (MT) may be involved in chronic immune activation, which plays a central role in HIV pathogenesis. Th17 cells are critical to prevent MT. The aim of the study was to investigate, in patients with primary HIV infection (PHI), the early relationship between the Th17/Treg ratio, monocyte activation and MT and their impact on the T-cell activation set point, which is known to predict disease progression. 27 patients with early PHI were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 61 publications
11
88
1
1
Order By: Relevance
“…16,33,34 Altered gut-homing Treg:Th17 and Th1:Treg ratios were documented during chronic HIV-1 infection despite ART. 25 Abnormal ratios of Th1:Treg and Treg:Th17 were also demonstrated in AHIs (Figure 6b and 6c).…”
Section: Discussionmentioning
confidence: 99%
“…16,33,34 Altered gut-homing Treg:Th17 and Th1:Treg ratios were documented during chronic HIV-1 infection despite ART. 25 Abnormal ratios of Th1:Treg and Treg:Th17 were also demonstrated in AHIs (Figure 6b and 6c).…”
Section: Discussionmentioning
confidence: 99%
“…They have been reported to be upregulated in HIV infection and can act as predictive markers of HIV disease progression. [1][2][3][4][5][6] Increased coagulation biomarkers, such as Ddimer and/or thrombin-antithrombin complex, were also found to be correlated with sCD14 in pathogenic simian immunodeficiency virus infection. 41 In addition, we found that increased plasma levels of sCD14 and sCD163 were positively correlated with HIV-1 viremia, but were negatively correlated with the CD4 counts.…”
Section: Cd16mentioning
confidence: 94%
“…As markers of immune activation, the plasma sCD14 and sCD163 levels are elevated during HIV-1 infection and are useful in predicting the activation status of the monocyte response, HIV activity and pathogenesis. [1][2][3][4][5][6] Toll-like receptors (TLRs) are abundantly expressed on monocytes and are involved in innate monocyte responses. Many studies suggested that TLR responses contribute to the disease progression and clinical outcomes of viral infections, including HIV infections.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of GHRH on innate and cellular immune activation is still unclear. attributed to microbial translocation does not correspond entirely to markers of mucosal integrity or damage [15,32]. Despite the initiation of ART and plasma viral suppression, defects in junctional complex expression, the presence of bacterial products in the lamina propria, and reduced interleukin 17 (IL-17)-and (IL-22)-producing cells persist in treated HIV infection [28,33], and even the early initiation of ART shortly after infection does not fully normalize gastrointestinal mucosal dysfunction markers [34].…”
Section: Cd4mentioning
confidence: 99%